(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
Background: Nowadays litigation and allegations are increasing in India and Ophthalmologists are at very high risk to encounter this issue, major and serious complications can end up in loss of eye sight or even eye, which are often referred to as grievous injury by court of law. Aims and Objectives: The present study throws light on various aspect and reasons leading to litigation and allegations, pattern of medical negligence and also the pattern of compensation awarded by various forums pertaining to cataract surgery, which is off course the most commonly performed ocular surgery in India and across the world. Material and Methods: The National consumer dispute redressal commission (NCDRC) decided 942 cases of all speciality from year 2002 to February 2018 out of these 30 judgement of alleged medical negligence cases are related to ophthalmology, out of which we have included 11 cases of cataract surgery. Results: Out of these 11 cases, in 4 cases (36.36%) medical negligence is proved before NCDRC and compensation is awarded and endophthalmitis is found to be most common cause leading to litigation. Highest compensation awarded is 9 crore 85 lacs and lowest is 20 thousand. In most of the cases leading to litigation, in 50% cases the pre-existing ocular and systemic comorbidity is present. In this era where more and more patient are getting aware of their rights and number of litigations are increasing at higher rate, this has pushed the doctor to defensive mode and make hi practice in a more safer way, which could be detrimental to society in near future. Therefore there is need to establish a balance between patient’s right and professional honesty. Conclusions: The results of this study will help in improving the standards and quality of health care services and will strengthen the doctor-patient relationship and will make the doctor think about reviewing his/her pattern of practice and this will finally benefit the society.